Blupages directory engineering & maintenance. (Blupages International, Inc., 1993)
The Bluepages Directory is a helpful reference material for technical and engineering data. It outlines about 10,000 entries of engineering and technical data, information about some major engineering/technical associations and a listing of "PS Mark" bearers by the Bureau of product standards of the Department of Trade and Industry. This third to edition caters the industrial needs, international and local.